Performance of Commercial Broilers under Separate Sex Rearing and Feeding during the Finisher Period - Lonkar, Vijaysinh D.; Kadam, Avinash S.; Patodkar, Vishwambhar R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The performance of commercial broiler chicken was evaluated under separate sex rearing and feeding during the finisher stage (22-42 days age). A total of 210, (21 days-old) commercial broilers were randomly allocated to five groups, viz., A (male & female mixed), B (male), C (male), D (female), and E (female) containing 42 birds in each group. The birds from groups A, C, and E were fed with a commercial broiler finisher diet containing 3250 kcal ME/kg, 19.5% CP, 1.00% Dig. Lysine (Dig. Lys) and 0.49% Dig. Methionine (Dig, Met). The males in group B were fed a special male diet containing 3000 kcal ME/kg, 18% Crude Protein (CP), and females from group D were fed a special female diet containing 3100 kcal ME/kg, 19.5 % CP. The Dig. Lys and Dig. Met levels in group B and D finisher diets were 2% higher than in group A. The results of the study concluded that the separate sex rearing of broilers may be followed by feeding special finisher diets to males (B) and females (D) to achieve similar body weight, weight gain, and feed efficiency to that of males (C) and females fed with a commercial finisher diet. Separate sex rearing of commercial broilers with special feeding is more economical than commercial diets fed to mixed and separate sex. Females fed on a special finisher diet had significantly (P < .05) higher serum total protein, albumin, and A/G ratio than males fed on a special finisher diet.